Cooperative Mechanism of ADAMTS/ ADAMTSL and Fibrillin-1 in the Marfan Syndrome and Acromelic Dysplasias - Arnaud, Pauline; Mougin, Zakaria; Boileau, Catherine; Le Goff, Carine (Frontiers in Genetics, 2021)
The term ”fibrillinopathies” gathers various diseases with a wide spectrum of clinical features and severity but all sharing mutations in the fibrillin genes. The first described fibrillinopathy, Marfan syndrome (MFS), is a multisystem disease with a unique combination of skeletal, thoracic aortic aneurysm (TAA) and ocular features. The numerous FBN1 mutations identified in MFS are located all along the gene, leading to the same pathogenic mechanism. The geleophysic/acromicric dysplasias (GD/AD), characterized by short stature, short extremities, and joint limitation are described as “the mirror image” of MFS. Previously, in GD/AD patients, we identified heterozygous FBN1 mutations all affecting TGFβ-binding protein-like domain 5 (TB5). ADAMTS10, ADAMTS17 and, ADAMTSL2 are also involved in the pathogenic mechanism of acromelic dysplasia. More recently, in TAA patients, we identified mutations in THSD4, encoding ADAMTSL6, a protein belonging to the ADAMTSL family suggesting that ADAMTSL proteins are also involved in the Marfanoid spectrum. Together with human genetic data and generated knockout mouse models targeting the involved genes, we provide herein an overview of the role of fibrillin-1 in opposite phenotypes. Finally, we will decipher the potential biological cooperation of ADAMTS-fibrillin-1 involved in these opposite phenotypes.